Attenuation of fibroblast growth factor signaling by poly‐N‐acetyllactosamine type glycans. Issue 19 (19th August 2013) - Sugihara, Kazuhiro; Shibata, Toshiaki K.; Takata, Kayoko; Kimura, Takako; Kanayama, Naohiro; Williams, Roy; Hatakeyama, Shingo; Akama, Tomoya O.; Kuo, Chu-Wei; Khoo, Kay-Hooi; Fukuda, Michiko N.
Abstract : Fibroblast growth factors (FGFs) and their receptors are expressed in a variety of mammalian tissues, playing a role in development and cell proliferation. While analyzing human sperm motility, we found that sperm treated with endo‐β‐galactosidase (EBG), which specifically hydrolyzes poly‐ N ‐acetyllactosamine type glycans (polyLacs), enhanced motility. Mass spectrometry analysis revealed that sperm‐associated polyLacs are heavily fucosylated, consistent with Lewis Y antigen. Immunohistochemistry of epididymis using an anti‐Lewis Y antibody before and after EBG treatment suggested that polyLacs carrying the Lewis Y epitope are synthesized in epididymal epithelia and secreted to seminal fluid. EBG‐treated sperm elevated cAMP levels and calcium influx, indicating activation of fibroblast growth factor signaling. Seminal fluid polyLacs bound to FGFs in vitro, and impaired FGF‐mediated signaling in HEK293T cells. Abstract : We found that human sperm treated with endo‐β‐galactosidase enhanced motility. Sperm‐associated poly‐ N ‐acetyllactosamine type glycans are heavily fucosylated. We found that fucosylated glycans are synthesized in epididymis. We found fibroblast growth factors bind to poly‐ N ‐acetyllactosamine type glycans.